Chronic Wound Healing by Amniotic Membrane: TGF-β and EGF Signaling Modulation in Re-epithelialization - Ruiz-Cañada, Catalina; Bernabé-García, Ángel; Liarte, Sergio; Rodríguez-Valiente, Mónica; Nicolás, Francisco José (Frontiers in Bioengineering and Biotechnology, 2021)
The application of amniotic membrane (AM) on chronic wounds has proven very effective at resetting wound healing, particularly in re-epithelialization. Historically, several aspects of AM effect on wound healing have been evaluated using cell models. In keratinocytes, the presence of amniotic membrane induced the activation of mitogen activated protein (MAP)-kinase and c-Jun-N-terminal kinase (JNK) pathways together with the high expression of c-Jun, an important transcription factor for the progression of the re-epithelialization tongue. In general, the levels of transforming growth factor (TGF)-β present in a wound are critical for the process of wound healing; they are elevated during the inflammation phase and remain high in some chronic wounds. Interestingly, the presence of AM, through EGF signaling, produces a fine-tuning of the TGF-β signaling pathway that re-conducts the stalled process of wound healing. However, the complete suppression of TGF-β signaling has proven negative for the AM stimulation of migration, suggesting that a minimal amount of TGF-β signaling is required for proper wound healing. Regarding migration machinery, AM contributes to the dynamics of focal adhesions, producing a high turnover and thus speeding up remodeling. This was already clear because proteins such as Paxillin are activated upon treatment with AM. On top of this, AM also produces changes in the expression of Paxillin. Although we have made great progress in understanding the effects of AM on chronic-wound healing, a long way is still ahead of us to fully comprehend its effects.